Studying the rate of polyphenol oxidase activity in apples using a colorimeter - Chandrasekhar, Shreya (Open Science Journal, 2021)
Salt is one of the oldest methods used to preserve food and help it stay fresh by preventing rotting due to its antibacterial properties. This study was therefore conducted to understand how the increase in salt concentration affects the rate of change of polyphenol oxidase activity in apples using a colorimeter. A colorimeter is a device used to measure absorbance of particular wavelengths of light by specific solutions, in this case, Granny Smith Apple juice. The results correlated with the hypothesis which is predicted that as the salt concentration of the dilutions increase, there will be a decrease in the rate of change of absorbance because the chlorine ions from the salt will inhibit the polyphenol oxidase activity and prevent further oxidation of phenols to quinones, limiting the polymerization and formation of melanin. The results confirm that salt is a non-competitive inhibitor of polyphenol oxidase because it slows down the catabolic processes in apples- mainly the breakdown of glucose. However, salt is a non-competitive inhibitor of PPO but as for lower concentrations, such as 0.25M and 0.50M, the higher concentration of substrates still mitigates the effect of salt as an inhibitor to a significant extent.